Application of multiple γ-ray detection to long-lived radioactive nuclide determination in environmental samples. Issue 6 (2nd June 2020) - Oshima, Masumi; Goto, Jun; Haraga, Tomoko; Kin, Tadahiro; Ikebe, Yurie; Seto, Hirofumi; Bamba, Shigeru; Shinohara, Hirofumi; Morimoto, Takao; Isogai, Keisuke
ABSTRACT: Gamma-gamma coincidence measurement utilized in γ-ray spectroscopy experiments is well known to be effective for the improvement of signal-to-noise ratio in a γ-ray spectrum. We study its applicability to the determination of long-lived radioactive nuclides in environmental samples. The γ-ray simulation code Geant 4.10.2 was used. A conventional and effective detector system comprising five Ge detectors was assumed. We took up 38 nuclides which need to be determined for the evaluation of fission product leakage at the nuclear accident in the Fukushima nuclear power plants in Japan. Among them 12 nuclides emit γ-rays and five nuclides of 60 Co, 94 Nb, 134 Cs, 152 Eu, and 154 Eu can be the objectives of the multiple γ-ray detection methods. The simulation results indicate that the signal-to-noise ratio can be improved by a factor between 9.84 and 283, and the detection limit by a factor between 2.71 and 8.53 relative to the singles measurement, implying that the method can be well applied to the determination of the long-lived radioactive nuclides and will provide a quick and non-destructive analysis method.